Digital communications : - Sklar, Bernard (Prentice-Hall PTR, 2001)
Digital Communications, Second Edition is a revised and updated edition of the field’s classic, best-selling introduction. With remarkable clarity, Drs. Bernard Sklar and fred harris introduce every digital communication technology at the heart of today's wireless and Internet revolutions, with new chapters on synchronization, OFDM, and MIMO.